2017
DOI: 10.1016/j.gaitpost.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Attention is associated with postural control in those with chronic ankle instability

Abstract: Chronic ankle instability (CAI) is often debilitating and may be affected by a number of intrinsic and environmental factors. Alterations in neurocognitive function and attention may contribute to repetitive injury in those with CAI and influence postural control strategies. Thus, the purpose of this study was to determine if there was a difference in attentional functioning and static postural control among groups of Comparison, Coper and CAI participants and assess the relationship between them within each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Furthermore, three recent studies found that decreased cognitive function may be related to CAI. Rosen et al [8] reported a strong relationship between attentional control and single-leg center of pressure (COP) measures, which was not present in non-injured controls. However, there were no differences between the groups in the measures of attention or COP.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three recent studies found that decreased cognitive function may be related to CAI. Rosen et al [8] reported a strong relationship between attentional control and single-leg center of pressure (COP) measures, which was not present in non-injured controls. However, there were no differences between the groups in the measures of attention or COP.…”
Section: Introductionmentioning
confidence: 99%
“…If one or more of these systems fail, or the sensory information is not correctly processed, the risk of a fall or instability increases. As balance is the foundation for all voluntary motor skills, considerable research has been conducted to evaluate the balance performance in patients with low back pain 3 , 4 , 5 , 6 ) , anterior cruciate ligament injury 7 , 8 ) , and chronic ankle instability 9 , 10 ) . Many variables have been developed from force platform signals to quantify postural steadiness.…”
Section: Introductionmentioning
confidence: 99%
“…This is based on the theory that injuries are most likely to occur when individuals are physically and mentally fatigued, thinking about multiple items (eg, where to run or pass the ball, what play is next), startled, or otherwise distracted. [84][85][86] As cognitive resources are dedicated to other tasks, individuals often lose the concentration that may be needed to stabilize the lower extremity. New evidence 84,86 supported the use of cognitive training in prevention and rehabilitation programs, such as performing cognitive tasks during balancing exercises or incorporating choices and decision making into dynamicstabilization tasks.…”
Section: Emerging Prevention Techniquesmentioning
confidence: 99%